DIGITAL TRANSFORMATION AND ITS IMPACT ON ECONOMIC GROWTH: A CASE STUDY OF SAUDI ARABIA AND THE POTENTIAL FOR LEVERAGING IT IN IRAQ - Zinah Khudhair mhmood (Scholar Express Journals, 2025)
This study aims to examine the impact of digital transformation indicators on economic growth in Saudi Arabia and explore the potential for leveraging these insights in Iraq. The research analyzes the relationship between broadband subscriptions, the percentage of internet users among the population, mobile phone subscriptions, and Gross Domestic Product (GDP). Adopting a quantitative analytical approach, the study employs a multiple linear regression model using the Ordinary Least Squares (OLS) method to test the research hypotheses. The findings indicate that the percentage of internet users has a significant and positive impact on economic growth, whereas the effects of broadband subscriptions and mobile phone subscriptions are less pronounced. This highlights the importance of enhancing digital inclusion policies and investing in digital infrastructure to support economic development. Furthermore, the study emphasizes the need for comprehensive national strategies to foster digital transformation, contributing to sustainable economic growth in the long term.
Keywords: Digital transformation; economic growth; broadband subscriptions